ALTERNATIVE OF MONETARY POLICY INDICATOR: PANEL DATA ANALYSIS FROM ISLAMIC BANKS IN MALAYSIA - Ahmad, Zuriyati; Ismail, Abdul Ghafar (Journal of Islamic Monetary Economics and Finance, 2019)
The monetary policy indicators such as monetary aggregates, interest rates and Monetary Condition Index (MCI) are the traditional monetary policy indicators used in order to obtain early indication of the impact of monetary policy. These indicators could function as appropriate monetary policy indicators that will provide information to the monetary policy makers. The development in Islamic financial system however creates a challenge to find a monetary policy indicator, which is in conformity with Islamic teaching. Therefore, this paper is aimed to examine the future growth of nominal GDP as an alternative variable for monetary policy indicator in Islamic monetary system. The investigation will benefit from data of 17 Islamic banks in Malaysia which implement full fledge or Islamic windows scheme spanning from 2005 to 2010. GMM system method is used to analyze the data in hope to validate the appropriateness of the alternative monetary policy indicator. The result suggests that the future growth of nominal GDP is significant as monetary policy indicator and could be applied by the central bank in implementing the monetary policy especially in the dual banking system.